TINJAUAN HUKUM ISLAM PADA EDARAN PEMERINTAH DAN MUI DALAM MENYIKAPI WABAH COVID-19 - Alif Jumai Rajab; Muhamad Saddam Nurdin; Hayatullah Mubarak (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
The research is talking about a virus spread across the world with her being taken from the government and MUI as the Islamic regime. The government itself has issued a hand-to-hand lockdown system and also a PSBB or social distaff to fight the spread of the virus covid-19, so is the counter measures done by MUI by canceling traditional player in the mosque and by reducing Friday prayer in regular. Even though this circular became a pro and cons for most of society especially at the rings of MUI. The purpose of this research is to help the public understand whether the government?s existence and MUI?s treatment of the plague corresponds to or even contradicts the Islamic regime. Research methods will be used with literature literature review with the normative approarch and supported by the historial approach. Research shows that the rule imposed by the government and MUI in handling the outbreak did not include an investigation into Islam.